Combined Effects of Cypermethrin and Lead on Biochemical and Molecular Parameters in Albino Mice - Jaffer, Noor S.; Rabee, Adel M. (Iraqi Journal of Science, 2024)
In this study, the combined toxicity of cypermethrin and lead were investigated using molecular and biochemical parameters in albino mice. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP),blood urea nitrogen (BUN) and creatinine levels were studied and used as indicators of toxicity. Comet test was also utilized to evaluate the mechanism of genotoxicity of cypermethrin, lead and the ) cypermethrin and lead) group. Albino mice were divided into eight groups and given intraperitoneal cypermethrin injections at 1.75 mg/kg/day and lead nitrate at 1.75 mg/kg/day, and combined doses of each one respectively. Blood samples were collected after two and four weeks. Cypermethrin raised AST, AL, BUN and creatinine levels as treatment time and doses rose, as did lead nitrate which elevated liver and kidney parameters in response to the toxicant. As evaluated by comet test molecular characteristics, the impact of cypermethrin and lead nitrate was an increase in DNA damage.